Paving the Public Street Path to Ensure Safe Movement for The Blind: An Applied Study in the Ard Sultan Area in Minia City تمهيد مسار الطريق العام بصورة تضمن الحركة الآمنة لكفيف البصر "دراسة تطبيقية على منطقة أرض سلطان في مدينة المنيا - Amna Waz (JES: Journal of Engineering Sciences)
The movement of the blind in the streets is considered one of the first difficulties He faces when he wants to interact with his community. Therefore, the research problem is that movement paths in Egyptian cities need to be paved to be easier and safer for the movement of the blind. The research aimed to explore how to overcome obstacles in movement paths, so that the blind can go down to practice his live, as a kind of response to the recommendation of the executive regulations of the Law on the Rights of Persons with Disabilities to facilitate their participation. The research relied on the inductive approach in identifying the features of the movement paths welcoming the blind from the perspective of inclusive urban design for the blind. The analytical field approach was used when exploring any longitudinal path in Ard Sultan in Minia City that is suitable for paving the way to accommodate the movement of the blind. A list of criteria suggested by the research and the SPSS program were used in this. The deductive approach was applied in the research results and recommendations. الملخصتعتبر حركة كفيف البصر في الشوارع من أول الصعوبات التي تواجه كفيف البصر، عندما يرغب في الاحتكاك المادي بمجتمعه، وبالتالي تتمثل المشكلة البحثية في احتياج مسارات الحركة بالمدن المصرية للتمهيد لتكون أيسر وآمن لحركة كفيف البصر. استهدف البحث استكشاف كيفية تذليل العقبات أمام الكفيف في مسارات الحركة فى عمران المدن، ليتمكن من النزول لممارسة حياته، كنوع من الاستجابة لتوصية اللائحة التنفيذية لقانون حقوق الأشخاص ذوي الإعاقة بتيسير مشاركاتهم.قد اعتمد البحث على المنهج الاستقرائي خلال التعرف على سمات مسارات الحركة المرحبة بالكفيف في إطار توجه التصميم العمراني الشامل لفئة الكفيف. استخدم المنهج الميداني التحليلي عند استكشاف أي مسار طولي بمنطقة تقسيم أرض سلطان في مدينة المنيا ملائم لتمهيد ليستوعب حركة الكفيف، وتم الاستعانة في ذلك بقائمة معايير اقترحها البحث وبرنامج الـ SPSS. طبق المنهج الاستنباطي عند صياغة النتائج والتوصيات البحثية.